2018
DOI: 10.1186/s12879-018-2945-8
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring vaccine and non-vaccine HPV type prevalence in the post-vaccination era in women living in the Basilicata region, Italy

Abstract: BackgroundA large free-of-charge quadrivalent HPV (qHPV) vaccination program, covering four cohorts annually (women 11, 14, 17 and 24 years), has been implemented in Basilicata since 2007. This study evaluated vaccine and non-vaccine HPV prevalence 5-7 years post-vaccination program implementation in vaccinated and unvaccinated women.MethodsThis population-based, cross-sectional study was conducted in the public screening centers of the Local Health Unit in Matera between 2012 and 2014. Cervical samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
3
34
1
Order By: Relevance
“…We found a statistically significant difference in the prevalence of high-risk genotypes (6/11/16 and 18) between vaccinated and unvaccinated young women. These findings confirm the results of other studies on the effectiveness of the HPV vaccination as a means to decrease the prevalence of vaccine-targeted HPV types [ 13 , 14 , 15 , 16 ]. On the other hand, we observed no cross-protection for the other HPV genotypes, as we found no significant difference in the prevalence of non-Gardasil targeted genotypes between vaccinated and unvaccinated women, similar to other studies on the subject [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…We found a statistically significant difference in the prevalence of high-risk genotypes (6/11/16 and 18) between vaccinated and unvaccinated young women. These findings confirm the results of other studies on the effectiveness of the HPV vaccination as a means to decrease the prevalence of vaccine-targeted HPV types [ 13 , 14 , 15 , 16 ]. On the other hand, we observed no cross-protection for the other HPV genotypes, as we found no significant difference in the prevalence of non-Gardasil targeted genotypes between vaccinated and unvaccinated women, similar to other studies on the subject [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Other methods maybe be less sensitive, consistent with the lower prevalences reported for Latin America and Caribbean region in high-grade squamous intraepithelial lesions (41–67%) ( Parkin et al, 2008 ). High HPV prevalence ranging from 30 to 50% have been reported for other high-risk Latin American countries, using the same genotyping method SPF 25 /LiPA 10 , including anal specimens in Costa Rica ( Castro et al, 2012 ), and vaginal specimens in Surinam ( Geraets et al, 2014 ), as well as for Nigeria ( Adebamowo et al, 2017 ), Turkey ( Barut et al, 2018 ), and Italy ( Carozzi et al, 2018 ). The very high prevalence found in our study may reflect the high-risk patients from the San Juan Municipality, known to have rising cervical cancer diagnoses ( Registro Central De Cáncer De Puerto Rico, 2017 ).…”
Section: Discussionmentioning
confidence: 88%
“…26 Carozzi et al found no statistically significant differences in nonvaccine-type HPV in unvaccinated vs. vaccinated women after vaccine introduction in Italy, suggesting no evidence of type replacement. 25 In contrast, among a sample of 3,183 Finnish women, Merikukka et al demonstrated a possible competitive advantage for HPV33 over other genital HPV types in the unvaccinated population, and suggested that HPV33 should be monitored for type replacement after widespread HPV vaccination. 19 Table 3.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have similarly found no conclusive evidence of type replacement in realworld settings, but some have identified signals that confirm the importance of continued surveillance. [18][19][20][21]25,26 Yang et al examined concurrence of multiple HPV infections in 47,617 women undergoing cervical cancer screening, and found a negative interaction between HPV16 and other HPV types among women with abnormal cytology, but not among those with normal cytology, suggesting that type replacement in vaccinated women is unlikely in the general population. 21 Tota et al compared acquisition and clearance of 30 HPV types, using data from three studies involving 3200 women.…”
Section: Discussionmentioning
confidence: 99%